Change in functional status associated with respiratory syncytial virus infection in hospitalized older adults. Issue 6 (7th September 2022) - Branche, Angela R.; Saiman, Lisa; Walsh, Edward E.; Falsey, Ann R.; Jia, Haomiao; Barrett, Angela; Alba, Luis; Phillips, Matthew; Finelli, Lyn
Abstract: Background: Respiratory syncytial virus (RSV) causes severe respiratory illnesses in infants and older adults. Older adults are frequently hospitalized with RSV illness and may experience loss of function. This study evaluated longitudinal changes in function associated with RSV hospitalization in older adults. Methods: Adults ≥60 years hospitalized with laboratory‐confirmed RSV were enrolled (N = 302). Demographics and comorbidities were collected. Functional status was assessed 2 weeks pre‐hospitalization by recall, at enrollment, hospital discharge and 2, 4, and 6 months post‐discharge using the Lawton–Brody Instrumental Activities of Daily Living (IADL) (scale 0–8) and Barthel ADL Index (scale 0–100). Results: RSV‐associated hospitalization resulted in acute functional loss. Median IADL (5 vs. 3, p < 0.0001) and ADL (90 vs. 70, p < 0.0001) scores decreased significantly from pre‐hospitalization to admission and remained decreased at discharge. There were no statistically significant differences between pre‐hospitalization and 2‐, 4‐, or 6‐month scores. However, 33% and 32% of subjects experienced decreased 6‐month IADL and ADL scores, respectively. Additionally, 14% required a higher level of care at discharge. When stratified by pre‐hospitalization living situation, 6‐month IADL scores declined significantly for those admitted from a skilled nursing facility (3 vs. 1, p = 0.001). In multivariate analysis, male sex and diabetes were associated with a 6‐month decline in ADL score of ≥10. Conclusions: Older adults hospitalized with RSV demonstrate acute functional decline that may become prolonged. Pre‐hospitalization living situation may predict patient outcomes. Further study is needed with hospitalized age‐matched controls and refined measurement tools to better define the specific impact of RSV on function.